Bribery and corruption: Australian managers' experiences in international markets - Pedigo, Kerry; Marshall, Verena; Klass, Desmond (University of Melbourne, 2004)
Managers in cross-cultural settings inevitably face ethical dilemmas based on inconsistent cultural norms and while seeking to respect the local culture, may find themselves faced with conflicting values (De George 1993). The question of whose ethics or values should be applied or whether a set of universal ethical norms should be developed often confronts managers in their international business dealings. This paper explores the findings from a qualitative research study that set out to determine the critical ethical dilemmas confronting Australian managers in their international business operations and their responses to those dilemmas. For Australians managers in this study, bribery emerged as the major ethical dilemma confronting them in their international operations.